Madeleine Irish - A thesis submitted in partial fulfilment of the requirements of the degree of Doctor of Clinical Psychology (DClinPsych) - Irish, M (2023)
Critical review of the literature: Personality as a predictor of biological and psychological outcomes in bariatric surgery amongst an adult population: a systematic review.